The residue of trenbolone from male Garut sheep which implanted by trenbolone acetate - Widiastuti, R; ., Indraningsih; Murdiarti, T.B; Firmansyah, R (Indonesian Animal Sciences Society, 2001)
Trenbolone acetate (TBA) is a growth hormone promoter which is implanted into animal to increase the body weight. The implantation of TBA in animal may cause the occurrence of residues of TBA and its metabolite (17-Î²-trenbolone). The presence of the residue might threat to human health. The aim of this research work was to study the presence of the residue of trenbolone in male Garut sheep which is implanted by TBA. The sheep were divided into 2 groups, those were D1 which were implanted by 40 mg TBA and D2 which were implanted by 60 mg TBA. One animal each from D1 and D2 were killed in the week 1, 2, 3 and 4 after implantation. And 24 hours before slaughtering the urine of D1 and D2 were collected using the metabolism cages. The samples for residue analysis were the organs such as liver, kidney, and the muscles around the implantation sites i.e inner and outer, upper front leg and upper back leg. The samples were extracted by organic solvents and analysed by HPLC. The residue of trenbolone occured in all samples of D1 and D2 which killed on 1 and 2 weeks after implantation. The residues occured on those which were killed 3 weeks after implantation were only in inner and outer samples. The residues in meat and organs were not detected in D1 nor D2 which were killed 4 weeks after implantation. The residue of trenbolone was also detected in the urine and still were detected in D1 and D2 which implanted by TBA for 4 weeks. Â Key words : trenbolone acetate, 17-Î²-trenbolone, residue, sheep